2007
DOI: 10.1177/0957926507082194
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and anti-whaling discourses in British and Japanese newspaper reports in comparison: a cross-cultural perspective

Abstract: This article compares and contrasts the discourse of whaling in British and Japanese newspaper reports. It investigates the ways in which pro- and anti-whaling discourses are formulated in the press by examining, in particular, the following features: (1) the use of specific lexis and syntactic structures, (2) the use of rhetorical devices, and (3) the control and organization of information at a discourse level. The article claims that British and Japanese news reports use very different strategies in express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It has been documented that the Japanese media lack independence, with an over-close relationship with government [34] existing in the form of the Kisha-Kurabu (reporters' club) present in every ministry and government agency. 18 Murata (2007) [36] notes that articles about whaling in the Japanese press are written in a factual style (although ''factual'' can also disguise a presentation that is essentially ''evaluative''), using non-emotive lexis tending to reflect official statements made by the GOJ. Many articles also attempt to convey a sense that whaling is not under threat and that it is not a contentious issue.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that the Japanese media lack independence, with an over-close relationship with government [34] existing in the form of the Kisha-Kurabu (reporters' club) present in every ministry and government agency. 18 Murata (2007) [36] notes that articles about whaling in the Japanese press are written in a factual style (although ''factual'' can also disguise a presentation that is essentially ''evaluative''), using non-emotive lexis tending to reflect official statements made by the GOJ. Many articles also attempt to convey a sense that whaling is not under threat and that it is not a contentious issue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that using intransitive verbs (including ergative verbs discussed in this study) can achieve the pragmatic purpose of avoiding accusations, and that native English speakers tend to be more confident in using ergative verbs when writing compositions (Sotillo & Starace-Nastasi 1999;Fang 2001;Berk-Seligson 2002;Kuo & Nakamura 2005;Lillian 2007;Murata 2007). However, these studies were largely based on analyzing texts from composition writing sources.…”
Section: Ergative Verbs and Accusation-avoidance Translation Strategiesmentioning
confidence: 90%
“…A great deal of research has been done on how to de-focus the agent of an action or process (Langacker 1987;Fang 1994;Gerbig 1997;Comrie 1989;Hagiwara 1992;Stubbs 1994;Sotillo & Starace-Nastasi 1999;Cai 2000;Fang 2001;Berk-Seligson 2002;Kuo & Nakamura 2005;Yu 2006;Mo 2006;Li 2007;Lillian 2007;Murata 2007). For example, Fang (1994) compared the editing and reporting strategies used by a Chinese government-funded English newspaper when covering news events in its 'friendly' countries against those in the 'hostile' ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…58 is explains why Kumiko Murata has also acknowledged that Japanese editorials on the whaling issue are written 'as if the writer is reporting an o cial statement on behalf of the Japanese government. ' 59 us, in the current environment, Japanese media only have limited options, and act as if they are public relations agencies for their government.…”
Section: Discussionmentioning
confidence: 99%